Active vibration control design using the Coral Reefs Optimization with Substrate Layer algorithm. (15th February 2018) - Camacho-Gómez, C.; Wang, X.; Pereira, E.; Díaz, I.M.; Salcedo-Sanz, S.
Highlights: The main existing problems of active vibration control are solved. The applicability of active vibration control for complex structures is improved. The human vibration perception and non-linear dynamics are considered. The recently proposed Coral Reefs Optimization with Substrate layer is used. A finite element model of a real complex floor structure is controlled. Abstract: Active vibration control (AVC) via inertial-mass actuators is a viable technique to mitigate human-induced vibrations in civil structures. A multi-input multi-output (MIMO) AVC has been previously proposed in the literature to simultaneously find the sensor/actuator pairs' optimal placements and tune the control gains. However, the method involved local gradient-based methods, which is not affordable when the number of possible locations of actuators is large. In this case, the computation time to obtain a local solution may be huge and unaffordable, which limits the number of test points and/or actuators/sensors considered. This paper proposes an alternative approach based on a recently proposed meta-heuristic, the Coral Reefs Optimization (CRO) algorithm. More concretely, an enhanced version of the CRO is considered, the Coral Reefs Optimization with Substrate Layer (CRO-SL). The CRO-SL is a competitive co-evolution algorithm in which different exploration procedures are jointly evolved within a single population of potential solutions to the problem. The proposed algorithm is thus able to promote competition among different search methods to solve hard optimization problems. In terms of structural design, this work provides an important step to improve the applicability of AVC systems to real complex structures (with a large number of vibration modes and/or with a large number of test points) by achieving global optimum designs with affordable computation time. A finite element model of a real complex floor structure is used to illustrate the contributions of this paper.